2019
DOI: 10.1021/acs.analchem.9b04263
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole Derivatives Improve Charge Reduction and Stabilization for Native Mass Spectrometry

Abstract: Noncovalent interactions between biomolecules are critical to their activity. Native mass spectrometry (MS) has enabled characterization of these interactions by preserving noncovalent assemblies for mass analysis, including protein–ligand and protein–protein complexes for a wide range of soluble and membrane proteins. Recent advances in native MS of lipoprotein nanodiscs have also allowed characterization of antimicrobial peptides and membrane proteins embedded in intact lipid bilayers. However, conventional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 38 publications
1
58
0
Order By: Relevance
“…EmbB was buffer exchanged into 0.2 M ammonium acetate at pH 6.8 (Sigma-Aldrich) with either 0.01% C12E8 (Anatrace) or 0.02% DDM (Anatrace) detergent using gel filtration. Native mass spectrometry (MS) analysis of EmbB in C12E8 detergent was performed using a Q-Exactive HF Orbitrap with Ultra High Mass Range modifications (Thermo Fisher Scientific) using previously described methods 70 . The HCD voltage was set to 150 V, and the capillary temperature was increased to 300°C.…”
Section: Resultsmentioning
confidence: 99%
“…EmbB was buffer exchanged into 0.2 M ammonium acetate at pH 6.8 (Sigma-Aldrich) with either 0.01% C12E8 (Anatrace) or 0.02% DDM (Anatrace) detergent using gel filtration. Native mass spectrometry (MS) analysis of EmbB in C12E8 detergent was performed using a Q-Exactive HF Orbitrap with Ultra High Mass Range modifications (Thermo Fisher Scientific) using previously described methods 70 . The HCD voltage was set to 150 V, and the capillary temperature was increased to 300°C.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid this preferential dissociation, we tested imidazole derivatives that have previously been shown to stabilize nanodisc complexes. 35 We found that 2-methylimidazole stabilized POPC/SOPE nanodiscs the most and caused POPC/SOPE nanodiscs to have higher mass distributions, indicating less dissociation (Figure 1). Interestingly, the average lipid mass shows that 2methylimidazole retained the labile SOPE up to 200 V applied in the HCD cell ( Figure S1).…”
Section: Resultsmentioning
confidence: 84%
“…The native mass spectra were deconvolved and quantified using UniDec, and macromolecular mass defect analysis was used to quantify the stoichiometries of AM2 and amantadine in nanodiscs. 39,50,51 Full details are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…The native mass spectra were deconvolved and quantified using UniDec, and macromolecular mass defect analysis was used to quantify the stoichiometries of AM2 and amantadine in nanodiscs. 41,61,62 Full details are provided in the Supporting Information. Prior published results with streptavidin, a similarly sized tetramer, with similar instrument conditions provided a positive control demonstrating the ability of native MS to preserve and detect specific noncovalent complexes of the same size.…”
Section: Native Mass Spectrometrymentioning
confidence: 99%